Pengaruh Akuntabilitas Pengelolaan Keuangan, Penerapan Standar Akuntansi, dan Sistem Pengendalian Intern terhadap Kualitas Laporan Keuangan (Studi Empiris pada Perusahaan LQ45 di Bursa Efek Indonesia Tahun 2020-2024) - Salmah, Saskia; Sari, Silvia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the influence of financial management accountability, the application of accounting standards, and the internal control system on the quality of financial reports. The research was conducted by analyzing the financial statements of LQ45 companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample consists of 13 LQ45 companies observed over five years, resulting in 65 total observations, selected using a purposive sampling technique. The data used in this study are secondary data in the form of financial reports from each sampled company. The analysis was performed using Eviews Student Version Lite software. The results show that financial management accountability, the application of accounting standards, and the internal control system simultaneously affect the quality of financial reports. Partially, the internal control system does not significantly influence the quality of financial reports, while financial management accountability and the application of accounting standards do have a significant effect. The Adjusted R² value of 0.362 indicates that 36.2% of the variation in financial report quality is explained by the three variables. The findings highlight the importance of strengthening financial management accountability and the application of accounting standards to improve the quality of financial reports. Theoretically, the results support agency theory, which states that high-quality financial reporting can minimize information asymmetry. However, the insignificant effect of the internal control system provides theoretical insight that the effectiveness of internal control in LQ45 companies may vary and is not always directly reflected in the quality of financial reporting.